Transcriptome analysis and co‐expression network reveal the mechanism linking mitochondrial function to immune regulation in red crucian carp (Carassius auratus red var) after Aeromonas hydrophila challenge - Xiong, Ning‐Xia; Kuang, Xu‐Ying; Fang, Zi‐Xuan; Ou, Jie; Li, Shi‐Yun; Zhao, Jia‐Hui; Huang, Jin‐Fang; Li, Ke‐Xin; Wang, Rou; Fan, Lan‐Fen; Luo, Sheng‐Wei; Liu, Shao‐Jun (Journal of fish diseases, 2022)
Aeromonas hydrophila is a common pathogen of freshwater fish. In this study, A. hydrophila infection was shown to cause tissue damage, trigger physiological changes as well as alter the expression profiles of immune‐ and metabolic‐related genes in immune tissues of red crucian carp (RCC). Transcriptome analysis revealed that acute A. hydrophila infection exerted a profound effect on mitochondrial oxidative phosphorylation linking metabolic regulation to immune response. In addition, we further identified cellular senescence, apoptosis, necrosis and mitogen‐activated protein kinase signal pathways as crucial signal pathways in the kidney of RCC subjected to A. hydrophila infection. These findings may have important implications for understanding modulation of immunometabolic response to bacterial infection.